The Role of the United Nations Security Council in the Protection of Cultural Heritage - Bagher Beidaghi; Peyman Bolouri; Malek Zolghader (پژوهشهای حقوقی)
Due to the various characteristics of cultural heritage, any attack on it draws the attention of the international community. This can be seen in the reactions of the United Nations (UN) to the destruction, looting, and trafficking of the cultural heritage of countries such as Iraq, Syria and the other countries committed by terrorist groups. What is important here is the United Nations Security Council's reactions to this issue. It seems that, in terms of securitizing cultural heritage, the procedures taken by the Security Council for the protection of cultural heritage have included requiring internal measures (affecting the domestic law of countries) and referring to the humanitarian aspects of cultural heritage. Paying attention to the Security Council’s performance with regard to cultural heritage can be effective since the Security Council, as the main pillar of the UN, has the primary duty of maintaining international peace and security and its decisions are binding for the UN members as per the UN Charter. To this end, this paper, by adopting a descriptive and analytical approach, tries to examine and explain the procedures of the United Nations Security Council for the protection of cultural heritage. Based on the findings of this paper, we conclude that United Nations Security Council’s resolutions have been effective in protecting cultural heritage.